2011
DOI: 10.1387/ijdb.103138dr
|View full text |Cite
|
Sign up to set email alerts
|

Tryptase and chymase are angiogenic in vivo in the chorioallantoic membrane assay

Abstract: Human mast cells (MCs) are divided in two types depending on the expression of tryptase and chymase in their granules. Literature data indicate that both tryptase and chymase are angiogenic, but there is currently no evidence of their direct angiogenic activity in vivo. In this study, we have investigated the capacity of tryptase and chymase to promote vasoproliferation in chick embryo chorioallantoic membrane (CAM), a well established in vivo assay to study angiogenesis and anti-angiogenesis. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 39 publications
4
41
0
1
Order By: Relevance
“…MMP-9, Collagenase, Gelatinase, Elastase (Fang et al, 1999;Bao Dang et al, 2013), MPO (Baldus et al, 2001;Shechter et al, 2011) Elastase (Kitson et al, 1998;Jacobsen et al, 2007) Tryptase Chymase (Weerth et al, 2003;Tchougounova et al, 2005), MMP-2, MMP-9 (Fang et al, 1999;Stirling et al, 2009) (Rahpeymai et al, 2006;Hao et al, 2010), BDNF, NT-3 (Hammarberg, et al 2000;Shinjyo et al, 2009) Sema4A, NT-3 (Bénard et al, 2008;Ishii et al, 2012) NAA (modulation of H 2 O 2 -induced apoptosis) (Warrington et al, 2004;Mantovani et al, 2011) Angiogenesis C5 (Norrby, 2002;Langer et al, 2010) VEGF (Scapini et al, 2004;Ribatti et al, 2011), MMP-9 (Justicia et al, 2003;Riboldi et al, 2005) PDGF, TNF-α and VEGF (Horiuchi and Weller, 1997) VEGF, TNF-α and β, FGF, MMP (Norrby et al, 2002) tryptase and chymase (Ribatti et al, 2011) VEGF (Riboldi et al, 2005), TNF-α, transdifferentiation in ELCs (Fernandez Pujol et al, 2001), trogocytosis of VEGF receptor …”
mentioning
confidence: 99%
“…MMP-9, Collagenase, Gelatinase, Elastase (Fang et al, 1999;Bao Dang et al, 2013), MPO (Baldus et al, 2001;Shechter et al, 2011) Elastase (Kitson et al, 1998;Jacobsen et al, 2007) Tryptase Chymase (Weerth et al, 2003;Tchougounova et al, 2005), MMP-2, MMP-9 (Fang et al, 1999;Stirling et al, 2009) (Rahpeymai et al, 2006;Hao et al, 2010), BDNF, NT-3 (Hammarberg, et al 2000;Shinjyo et al, 2009) Sema4A, NT-3 (Bénard et al, 2008;Ishii et al, 2012) NAA (modulation of H 2 O 2 -induced apoptosis) (Warrington et al, 2004;Mantovani et al, 2011) Angiogenesis C5 (Norrby, 2002;Langer et al, 2010) VEGF (Scapini et al, 2004;Ribatti et al, 2011), MMP-9 (Justicia et al, 2003;Riboldi et al, 2005) PDGF, TNF-α and VEGF (Horiuchi and Weller, 1997) VEGF, TNF-α and β, FGF, MMP (Norrby et al, 2002) tryptase and chymase (Ribatti et al, 2011) VEGF (Riboldi et al, 2005), TNF-α, transdifferentiation in ELCs (Fernandez Pujol et al, 2001), trogocytosis of VEGF receptor …”
mentioning
confidence: 99%
“…Using in ovo formalin-fixed specimens and histochemistry followed by microscopic evaluation, we demonstrated a highly angiotropic effect of mast cells early after inoculation. Although several studies have reported the angiogenic effects of mast cells and/or their granules on chick embryo chorioallantoic membrane (6,24,25), the angiogenic mechanism by which mast cells induce the development of new blood vessels in the chick embryo chorioallantoic membrane has not been clearly described. Evidence from our study suggests a complex mechanism of mast cell-induced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured tumor cells were washed in Dulbecco's PBS (DPBS) and 10 6 living cells in 100 mL PBS were inoculated below the chorioallantoic membrane. Inoculation was performed in a blood vessel-free area of the chick embryo chorioallantoic membrane to avoid hemorrhagic events.…”
Section: Cell Inoculation and Experiments Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, experimental studies showed the release of tryptase from mast cells to be a potent angiogenic factor, able to stimulate the neovascolarization both in vitro (16) and in vivo (17), and therefore directly involved in cancer cell proliferation. Consequently, human tryptase induces vascular tube formation either by direct mitogen action on endothelial cells (18)(19)(20)(21) or by indirect proteolytic action on the surrounding matrix (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%